Investing in children's health: what are the economic benefits? - Paolo C. Belli; Flavia Bustreo; Alexander Preker
This paper argues that investing in children's health is a sound economic decision for governments to take, even if the moral justifications for such programmes are not considered. The paper also outlines dimensions that are often neglected when public investment decisions are taken. The conclusion that can be drawn from the literature studying the relationship between children's health and the economy is that children's health is a potentially valuable economic investment. The literature shows that making greater investments in children's health results in better educated and more productive adults, sets in motion favourable demographic changes, and shows that safeguarding health during childhood is more important than at any other age because poor health during children's early years is likely to permanently impair them over the course of their life. In addition, the literature confirms that more attention should be paid to poor health as a mechanism for the intergenerational transmission of poverty. Children born into poor families have poorer health as children, receive lower investments in human capital, and have poorer health as adults. As a result, they will earn lower wages as adults, which will affect the next generation of children who will thus be born into poorer families.